2021
DOI: 10.1038/s41598-021-85853-8
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz refractive index-based morphological dilation for breast carcinoma delineation

Abstract: This paper reports investigations led on the combination of the refractive index and morphological dilation to enhance performances towards breast tumour margin delineation during conserving surgeries. The refractive index map of invasive ductal and lobular carcinomas were constructed from an inverse electromagnetic problem. Morphological dilation combined with refractive index thresholding was conducted to classify the tissue regions as malignant or benign. A histology routine was conducted to evaluate the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Terahertz time-domain spectroscopy (THz-TDS) has emerged as a noninvasive and objective tool for assessment of various biological tissue types, including determining corneal hydration 29 32 , diagnosis of brain tumors 33 35 , diabetic foot syndrome 36 , delineating breast cancer tumor margins 37 41 , and classification of burn injuries 42 , 43 . In burn diagnosis applications, it was shown that the reflectivity of the full-thickness burns in rodent models is higher compared to the normal skin over a frequency range between 0.2 and 1 THz 44 .…”
Section: Introductionmentioning
confidence: 99%
“…Terahertz time-domain spectroscopy (THz-TDS) has emerged as a noninvasive and objective tool for assessment of various biological tissue types, including determining corneal hydration 29 32 , diagnosis of brain tumors 33 35 , diabetic foot syndrome 36 , delineating breast cancer tumor margins 37 41 , and classification of burn injuries 42 , 43 . In burn diagnosis applications, it was shown that the reflectivity of the full-thickness burns in rodent models is higher compared to the normal skin over a frequency range between 0.2 and 1 THz 44 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study as reported in [119], the authors have used a combination of morphological dilation and refractive index thresholding to classify malignant and benign breast tissues so as to enhance the performance of tumor margin delineation for conserving surgeries. The image acquisition has been performed employing TPS3000 THz system in reflection mode.…”
Section: A: Materials and Methodsmentioning
confidence: 99%
“…In 2021, Cassar et al studied the combination of the refractive index and morphological dilation to improve performances towards breast tumor margin delineation during breast-conserving surgeries [ 92 ]. In this study, morphological dilation combined with the refractive index approach was applied for tissue classification.…”
Section: Chemometrics Methods In Thz Imagingmentioning
confidence: 99%